2015
DOI: 10.1097/mpa.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Liver Metastasis–Derived Cell Lines From KrasG12D; Trp53R172H; Pdx-1 Cre Animals Undergo Apoptosis in Response to Triptolide

Abstract: Objectives Pancreatic cancer has a five year survival rate of less than 5%, partly due to limited chemotherapeutic options, thereby highlighting the need for novel therapies. Triptolide, a diterpene triepoxide derived from a Chinese herb has shown great promise in preclinical testing against pancreatic cancer using immune compromised animals. Results In this study, we tested the ability of triptolide to induce cell death in cell lines derived from a primary tumor and adjacent liver metastases of immuno-compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Metastasis is the ultimate cause of death for most cancer patients. TP has been reported as an inhibitor of lung cancer cell migration and metastasis, but its mechanism is not clearly defined [12,57,58]. We observed some other differentially expressed proteins, such as MTA2 and E-cadherin (CDH1), implicated in cancer cell migration.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 69%
“…Metastasis is the ultimate cause of death for most cancer patients. TP has been reported as an inhibitor of lung cancer cell migration and metastasis, but its mechanism is not clearly defined [12,57,58]. We observed some other differentially expressed proteins, such as MTA2 and E-cadherin (CDH1), implicated in cancer cell migration.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 69%
“…The TECs were isolated according to our previous study(22). Isolation of CAFs (CAF-1, CAF-5 and CAF-7) from three KPC mice was performed following the protocol described by Sharon et al(26).…”
Section: Methodsmentioning
confidence: 99%
“…For ease of clinical application, we have developed a water-soluble prodrug, Minnelide for this compound (1722). Mechanistically, we have demonstrated that Minnelide downregulates HSP70 via inhibition of the activity of the transcription factor Sp1, thereby leading to pancreatic cancer cell death(23,24).…”
Section: Introductionmentioning
confidence: 99%
“…10 For animal experiments, KPC cell lines were trypsinized and resuspended in phosphate buffered saline/Matrigel in a 1:1 ratio. C57BL/6J mice were anesthetized, laparotomy was performed, and 50,000 cells were injected into the tail of the pancreas.…”
Section: Methodsmentioning
confidence: 99%